Paradigma Berekoteologi dan Peran Orang Percaya Terhadap Alam Ciptaan: Kajian Ekoteologi - Budiman, Sabda; Rutmana, Kiki; Takameha, Kristian Kariphi (Jurnal Borneo Humaniora, 2021)
Ecotheology is a discipline that discusses the relationship of God, man, with nature. In berekoteology the need for a proper and biblical paradigm as the basis for maintaining the environment. The problem formulation in this study is: What is the right and biblical paradigm in philoteology? What is the attitude of believers towards the nature of creation? The purpose of this writing is to describe the right and biblical paradigm in theology and explain the attitude of believers towards the nature of creation. This research uses qualitative method with descriptive approach. The result of the discussion is that believers should have a theocentric paradigm. In addition, believers play a role as stewardship, build solidarity with nature and be directly involved in the recovery of environmental crises.